Pengembangan Materi Ajar dan Penilaian Mata Pelajaran Ips pada Upt Smp Negeri 7 Alla Kabupaten Enrekang - Atji Sudarmaji (CV. Syntax Corporation Indonesia, 2023)
The objectives of this study: (1) knowing the development of teaching materials and their assessments in Integrated Social Studies subjects conducted by teachers at UPT SMP Negeri 7 Alla Enrekang Regency, (2) knowing the assessments in Integrated Social Studies subjects carried out by teachers at UPT SMP Negeri 7 Alla, (3) knowing the obstacles experienced and efforts to overcome them by teachers at UPT SMP Negeri 7 Alla Enrekang Regency. The research uses qualitative research methods with case study design. The informants in this study were social studies teachers, principals and also students at UPT SMP Negeri 7 Alla. Data collection techniques (1) observation, (2) interviews, (3) documents. Test the validity of the data using triangulation techniques and source triangulation. Research data is analyzed by interactive analysis, including data reduction, data presentation and drawing conclusions and verification. The results of this study show that the development of teaching materials carried out by teachers varies greatly in addition to looking for other sources from various books also develops by looking at the phenomena that occur in the environment around each school, besides that the development of teaching materials also focuses on the role of teachers who demand to be creative. The assessment carried out by teachers is formative and summative. Obstacles in material development and assessment are very diverse, ranging from obstacles in different source books, facilities that are less crowded and constraints from students themselves. And efforts to overcome these obstacles include efforts to improve and improve one's own abilities by learning alone or by exchanging ideas with fellow teachers and also in addition to external factors or internal factors such as system improvements and management in accordance with the obstacles experienced by each school